PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS LINGKUNGAN UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PADA MATERI PEMISAHAN CAMPURAN DAN ANALISIS DI SMK NEGERI 3 KABUPATEN BANTAENG - Akhmad Akhmad (Program Pasca Sarjana UNM, 2017)
This research is the development of (research and development), which includes the development of learning tools that is devoted to the development of learners' worksheets (LKPD) for material separation and analysis on Learners class XII SMK Negeri 3 Bantaeng Bantaeng. Development procedures used in this study is a model Thiagarajan consisting of four stages: define, design, develop and disseminate or adapted into a 4-D model is the definition, design, development and deployment. LKPD based environments are developed, validated by experts and practitioners and has undergone minor revisions to obtain decent results used. The results showed that the device STAD cooperative learning are valid, practical and effective. Worksheet learners (LKPD) used met the criteria of validity, namely the category of